2019
DOI: 10.1002/pmrj.12237
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Outcomes after Traumatic Brain Injury among Service Members and Veterans

Abstract: This scoping study describes the range of outcomes in traumatic brain injury (TBI) studies of military service members and veterans addressing gender differences. A secondary purpose is to identify differences in outcomes between male and female participants in such studies. We searched PubMed, CiNAHL, and PsycInfo databases for relevant articles. Two reviewers independently screened results. Of 822 unique titles and abstracts screened for eligibility, 55 full articles were reviewed, with 29 studies meeting fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…One clear conclusion was that women are very underrepresented; most of the studies were not specifically focused on gender differences, and women represented <20% of the sample. The most consistent finding to date was that following a TBI, females in the military are subsequently more susceptible to depression than male service members and veterans (16,19,45,79,80).…”
Section: Women and Military-related Tbimentioning
confidence: 96%
See 4 more Smart Citations
“…One clear conclusion was that women are very underrepresented; most of the studies were not specifically focused on gender differences, and women represented <20% of the sample. The most consistent finding to date was that following a TBI, females in the military are subsequently more susceptible to depression than male service members and veterans (16,19,45,79,80).…”
Section: Women and Military-related Tbimentioning
confidence: 96%
“…However, several studies comparing the outcomes of male and female service members following mTBI have reported differences in the frequencies of specific diagnoses and symptoms between men and women. In a recent scoping study describing the literature addressing gender differences in outcomes following TBI in military populations, Cogan et al (19) identified 29 relevant articles from 2000 to 2018. One clear conclusion was that women are very underrepresented; most of the studies were not specifically focused on gender differences, and women represented <20% of the sample.…”
Section: Women and Military-related Tbimentioning
confidence: 99%
See 3 more Smart Citations